2018
DOI: 10.1177/2055668317752088
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the validity of pressure-measuring insoles in quantifying gait variables

Abstract: Introduction Pressure-measuring insoles can provide a portable alternative to existing gait analysis tools. However, there is disagreement among researchers on their accuracy and the appropriate calibration methods. The purposes of this study were to (1) determine the validity of pressure-measuring insoles for calculating stance time and support-phase impulse during walking using two calibration procedures, and (2) examine the effect of insole size on the results. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 29 publications
1
29
0
Order By: Relevance
“…This overestimation was not reported in the validation studies done with other insoles. 6,26 The overestimated values could be explained by the sensitivity to the calibration procedure, which has already been shown by De Berardinis et al 26 for Medilogic ® insoles in healthy subjects. Another source of this discrepancy may lie in the difference in temperature inside the shoe between the prosthetic and contralateral limb, given that temperature is known to have an impact on measures.…”
Section: Discussionmentioning
confidence: 84%
“…This overestimation was not reported in the validation studies done with other insoles. 6,26 The overestimated values could be explained by the sensitivity to the calibration procedure, which has already been shown by De Berardinis et al 26 for Medilogic ® insoles in healthy subjects. Another source of this discrepancy may lie in the difference in temperature inside the shoe between the prosthetic and contralateral limb, given that temperature is known to have an impact on measures.…”
Section: Discussionmentioning
confidence: 84%
“…Compared to the values reported in literature-where only a few systems based on force-sensitive resistors have been characterized for timing performance-our system accurately estimated the stance duration, with good responsiveness in HS and TO recognition, in line with the results reported in previous studies. In the first case, previous studies demonstrated that the Medilogic ® insoles could estimate the stance duration with less than 10% error [40], while a system based on two footswitches performed the estimation with a ± 3% error [41]. Regarding gait-events recognition, the reported errors for in-shoe systems compared to force plates fell within 30 ms.…”
Section: Gait Event Recognitionmentioning
confidence: 83%
“…The most relevant parameters that can be calculated using the plantar pressure insoles were considered: Peak and Mean Pressure, the vertical component of the Ground Reaction Force (GRF), Center of Pressure (COP), the distance between COP and the origin (dCOP), and Contact Area. All data, except for the COP, were filtered using a 3rd order lowpass Butterworth filter with a cutoff frequency of 1/8 of the sampling frequency [ 33 ].…”
Section: Methodsmentioning
confidence: 99%